PENGARUH INTEGRITAS AUDITOR, KOMITMEN ORGANISASI, DAN PENGALAMAN KERJA AUDITOR TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (Studi terhadap persepsi auditor) - Syifa Amalia (2022)
This study aims to determine the effect of auditor integrity, organizational commitment, and work experience on the detection of financial statement fraud. The population of this study are auditors who work at the Supreme Audit Agency of the Republic of Indonesia (BPK RI). This study used purposive sampling and obtained as many as 63 auditors as respondents. This type of research is quantitative research using primary data obtained by distributing questionnaires via google form. The analysis carried out in this study was assisted by using the SmartPLS 3.0 application. The results of the tests that have been carried out can be concluded that: (1) auditor integrity has a positive and significant influence on fraud detection in financial statements, (2) organizational commitment has no effect on fraud detection in financial statements, (3) auditor work experience does not affect the detection of fraud in the financial statements.